The King James Bible as nationalist school curriculum amid immigration to the American West. Issue 1 (2nd January 2020) - Ritter, Luke
ABSTRACT: During the era of westward expansion, Americanism became tied to visions of conquering the West with American customs and values. Public schools especially served the interests of promoting nationalism and inducing assimilation. Implicitly Protestant Christian school curricula, however, repelled many Catholics and immigrants from the very institution designed to induce their assimilation. The mid-nineteenth-century school controversy directly motivated America's first political nativist movement, which associated Protestant Christianity with American greatness and promoted the mandatory use of the King James Bible in schools as the primary way to convert Catholics, Germans, and Irish to American national values.